Migration in the development studies literature: Has it come out of its marginality? - Arjan de Haan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper explores the role migration has played in development studies, and in debates on economic growth and poverty. It argues that, despite a recent surge of interest in international migration and remittances, research on human mobility particularly for labour within poor countries does not have the place it deserves, and that it used to have in the classical development literature. Review of the empirical literature suggests that in fact much is known about the migration–development relationship, provided we are careful with definitions, and allow for context-specificity to be a key component of analyses. Against this richness of empirical detail, the paper reviews theoretical models of migration, finding significant differences in understandings of migration and its role in shaping wellbeing, but also complementarities. This highlights the importance of interdisciplinarity, and institutional understanding of processes of economic growth. In particular, it stresses that development economics need to draw more strongly on the insights by and approaches of non-economist social sciences. – migration ; development studies ; growth
Keywords: J61; R23; 330; Entwicklungstheorie; Internationale Wanderung